SOCIOECONOMIC FACTORS OF YOUNG PERSONS' INVOLVEMENT IN THE SMUGGLING OF GOODS IN THE BADAGRY LOCAL GOVERNMENT AREA OF LAGOS, NIGERIA - Adedeji OYENUGA; Folawiyo, Abdulbasit; Opeyemi Kareem, Suliat; Esther, Adeola; Ameen, Mustapha; Eguaoje, Stella; Anigioro, Timothy; Onwuezi, Kingsley; Seyi Olaogun, Qudus (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
The smuggling of goods is a global issue with preponderance in most border communities worldwide. This paper is a qualitative examination of the socioeconomic factors of young persons' involvement in smuggling goods in the Badagry Local Government Area. The study used the Anomie Theory. Badagry is an ancient town that is also a border location between Nigeria and the Republic of Benin. Young persons between the ages of 15 and 35 years who are currently involved in the smuggling of goods and those who had in the past were purposively selected. Older people who engaged in smuggling at younger ages were also selected. Data were collected through the use of an In-depth Interview Schedule. They were analysed using content analysis and ethnographic summaries. The study found that the peculiar features of young persons involved in smuggling included keeping gangs and using voodoos, among others. That pseudonyms are created based on physique (Ijaya), position in the gang or Charisma (Apase), and others. The factors included unemployment, economic vulnerability, peer influence, family background, proximity to the border, and others. Finding also revealed that they tend to be involved in other crimes like substance consumption, burglary, and others. It is pertinent to state that smuggling is becoming more challenging, especially in the Internet age. As such, the government is responsible for providing employment and empowerment, the family practising stricter socialisation, especially at the border towns, and the security operatives become more vigilant.